Evidence for a geographical gradient selection in the distribution of breeding Podicipedidae and Rallidae in the south-western Mediterranean. Issue 37 (10th October 2018) - Cherkaoui, Sidi Imad; Hanane, Saâd
ABSTRACT: Knowledge of factors influencing waterbird distribution is a crucial step that would help wetland managers to target their conservation efforts. In this work, we used a 2-year survey in 25 wetlands distributed throughout Morocco to model Podicipedidae and Rallidae spatial distribution and to assess the relevance of a set of environmental and anthropogenic factors in predicting site occupancy, by means of generalised linear mixed models (GLMM). In Podicipedidae, little grebes and great crested grebes were the most commonly detected species, while in Rallidae the most common species was the common moorhen. Geographical location (measured mainly as distance to the coastline and elevation) was the major predictor of the occurrence probability of breeding Podicipedidae and Rallidae species in Morocco. Statistical analyses also provide evidence that there exists a geographical selection gradient in wetland occupancy. Indeed, Podicipedidae species (great crested grebes and black-necked grebes) tend to use continental mountain wetlands, while Rallidae (purple swamphens and Eurasian coots) tend instead to use coastal wetlands. However, none of the considered environmental and anthropogenic factors explained the distribution patterns of the red-knobbed coot. The pursuit of the investigations, while considering other explanatory factors such as water quality (limnological data), diet, predation and conservation status, is of great importance for understanding basic, large-scale geographical distribution patterns of Moroccan waterbird populations.